(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The use of immersive technologies in teaching the Russian language is a promising approach to modern education, which opens up new opportunities for stimulating interest and effectiveness in language learning. This paper examines the use of virtual reality and augmented reality in the context of Russian language teaching, taking into account their potential for creating immersive and interactive learning environments. Discusses the basic principles of using immersive technologies, such as virtual tours, educational applications, and real-life simulations, to improve Russian language comprehension and communication skills. Examples of the successful use of immersive technologies in educational programs are given, and the prospects and challenges of their implementation in modern Russian language teaching are discussed.